Patient perception of contemporary nurse attire: A pilot study. Issue 2 (23rd August 2013) - Porr, Caroline; Dawe, Doreen; Lewis, Nicole; Meadus, Robert J; Snow, Nicole; Didham, Paula
<x xml:space="preserve">Abstract</x> Patients have expressed difficulty accurately distinguishing registered nurses (RNs) from other hospital personnel because standardized uniforms are no longer worn by RNs. According to American studies, such complaints are widespread; moreover, patients' perceptions of nurse caring and competence and of other traits associated with nurses' professional image have been negatively affected by casual, non‐conventional attire. As there are no published Canadian studies, we conducted a pilot study to examine patient perception of the nurse uniform. Adult patients viewed photographs of the same RN dressed in eight different uniforms and rated each uniform according to 10 traits associated with nurses' professional image. The white pantsuit scored higher for professionalism than uniforms with small print, bold print, or solid colour, and most patients preferred that the RN dress in white. Our preliminary findings suggest that RN attire warrants further investigation, and we are planning a large‐scale, fully powered study to inform patient‐driven change to existing uniform policies.